Effects of V4c-ICL Implantation on Myopic Patients’ Vision-Related Daily Activities - Taixiang Liu; Shaorong Linghu; Le Pan; Rong Shi (Journal of Ophthalmology)
The new type implantable Collamer lens with a central hole (V4c-ICL) is widely used to treat myopia. However, halos occur in some patients after surgery. The aim is to evaluate the effect of V4c-ICL implantation on vision-related daily activities. This retrospective study included 42 patients. Uncorrected visual acuity (UCVA), best corrected visual acuity (BCVA), intraocular pressure (IOP), endothelial cell density (ECD), and vault were recorded and vision-related daily activities were evaluated at 3 months after operation. The average spherical equivalent was -0.12±0.33 D at 3 months after operation. UCVA equal to or better than preoperative BCVA occurred in 98% of eyes. The average BCVA at 3 months after operation was -0.03±0.07 LogMAR, which was significantly better than preoperative BCVA (0.08±0.10 LogMAR) (P=0.029). Apart from one patient (2.4%) who had difficulty reading computer screens, all patients had satisfactory or very satisfactory results. During the early postoperation, halos occurred in 23 patients (54.8%). However there were no significant differences in the scores of visual functions between patients with and without halos (P>0.05). Patients were very satisfied with their vision-related daily activities at 3 months after operation. The central hole of V4c-ICL does not affect patients’ vision-related daily activities.